2007
DOI: 10.4049/jimmunol.179.2.1274
|View full text |Cite
|
Sign up to set email alerts
|

Pyrin Levels in Human Monocytes and Monocyte-Derived Macrophages Regulate IL-1β Processing and Release

Abstract: Macrophages and their precursors, monocytes, are key cells involved in the innate immune response. Although both monocytes and macrophages produce caspase-1, the key enzyme responsible for pro-IL-1β processing; macrophages are limited in their ability to activate the enzyme and release functional IL-1β. In this context, because mutations in the pyrin gene (MEFV) cause the inflammatory disorder familial Mediterranean fever, pyrin is believed to regulate IL-1β processing. To determine whether variations in pyrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 42 publications
3
90
2
2
Order By: Relevance
“…In an in-vitro transfection model, wildtype pyrin acts as a proinflammatory molecule via the formation of a pyrin inflammasome complex [19]. A recent publication [20] is in keeping with this postulated pro-inflammatory role of pyrin, as it demonstrates that as monocytes differentiate into macrophages, pyrin protein expression diminishes with a parallel reduction in levels of IL-1β. All the above studies have been generated using in-vitro or murine models of disease, and the results may be explained by the changing role of pyrin depending on its cellular context.…”
Section: Advances In Our Understanding Of the Pathophysiology Of Monomentioning
confidence: 63%
“…In an in-vitro transfection model, wildtype pyrin acts as a proinflammatory molecule via the formation of a pyrin inflammasome complex [19]. A recent publication [20] is in keeping with this postulated pro-inflammatory role of pyrin, as it demonstrates that as monocytes differentiate into macrophages, pyrin protein expression diminishes with a parallel reduction in levels of IL-1β. All the above studies have been generated using in-vitro or murine models of disease, and the results may be explained by the changing role of pyrin depending on its cellular context.…”
Section: Advances In Our Understanding Of the Pathophysiology Of Monomentioning
confidence: 63%
“…Although pyrin does not share common domain architecture with NLRs, it has been shown to interact with ASC to form caspase-1-activating inflammasomes (37)(38)(39)(40). However, contrary to being an inflammasome activator, pyrin has also been suggested to function as a negative regulator of inflammasomes, because targeted disruption of pyrin in mice resulted in enhanced secretion of IL-1␤ (41).…”
Section: Other Inflammasome Modulatorsmentioning
confidence: 99%
“…Recently, NLRP2, NLRP6, NLRP7, RIG-I, pyrin, and IFI16 have been implicated in the formation of unique inflammasome complexes (4)(5)(6)(7)(8); however, additional investigation will be required to establish their precise roles in inflammasome formation and activation. Pyrin, mutations in which cause the autoinflammatory disease familial Mediterranean fever, can also form a caspase-1-activating inflammasome in concert with ASC (9,10). Interestingly, a recent study demonstrated that the Pyrin inflammasome is activated through the sensing of bacterial modification and inactivation of Rho GTPases (11).…”
Section: Introductionmentioning
confidence: 99%